포도 (Vitis labrusca L.)의 직접 재분화 방법을 이용한 식물체 재분화와 형질전환 - 김세희(Se Hee Kim); 신일섭(Il Sheob Shin); 조강희(Kang Hee Cho); 김대현(Dae Hyun Kim); 김현란(Hyun Ran Kim); 김정희(Jeong H (Journal of plant biotechnology, 2013)
Efficient regeneration methods and transformation system are a priority for successful application of genetic engineering to vegetative propagated plants such as grape (Vitis labrusca L.). This research is to establish shoot regeneration system from plant explants for 'Campbell Early', 'Tamnara', 'Heukgoosul', 'Heukbosek' using two types of plant growth regulators supplemented to medium. The highest adventitious shoot regeneration rate of 5% was achieved on a medium containing of Murashige and Skoog (MS) inorganic salts and Linsmaier and Skoog (LS) vitamins, 2 mg/L of TDZ and 0.1 mg/L of IBA. Leaf tissue of 'Campbell Early', was co-cultivated with Agrobacterium strains, LBA4404 containing the vector pBI121 carrying with CaMV 35S promoter, gus gene as reporter gene and resistance to kanamycin as selective agent, the other Agrobacterium strains, GV3101 containing the vector pB7 WG2D carrying with mPAP1-D gene. mPAP1-D is a regulatory genes of the anthocyanin biosynthetic pathway. 'Campbell Early' harboring mPAP1-D gene was readily able to be selected by red color due to anthocyanin accumulation in the transformed shoot. These results might be helpful for further studies to enhance the transformation efficiency in grape. 포도(Vitis labrusca L.)와 같은 영양번식 작물에서 성공적인 유전자 도입을 위해서는 효율적인 재분화 방법과 형질전환 체계 구축이 중요하다. 본 연구는 식물생장조절물질에 따른 두 가지 종류의 배지를 사용해서 포도의 신초 재분화 체계를 구축하였다. IBA 0.1 mg/L와 TDZ 2 mg/L, IBA 0.1 mg/L와 TDZ 2 mg/L의 조합에 Linsmaier and Skoog(LS) vitamin을 따로 첨가한 Murashige and Skoog (MS) 배지에서 '캠벨얼리', '탐나라', '흑구슬', '흑보석'의 재분화율을 조사하였더니 IBA 0.1 mg/L와 TDZ 2 mg/L를 첨가한 배지에서 '캠벨얼리'의 재분화율이 5%로 나왔다. '캠벨얼리'와 공동배양한 Agrobacterium strain은 CaMV 35S promoter와 GUS reporter 유전자, kanamycin에 저항성을 갖는 유전자가 있는 PBI121 vector가 도입된 LBA 4404와 안토시아닌 생합성을 조절하는 유전자로 알려진 mPAP1D유전자를 가지고 있는 pB7WG2D vector 가 도입된 GV3101이다. 포도와 같은 과수에서 형질전환체를 선발하는 방법으로 항생제 및 제초제 저항성을 대신할 수 있는 방법은 분자육종에 있어 매우 중요하다. mPAP1D유전자가 도입된 '캠벨얼리'의 재분화된 신초는 붉은색으로 쉽게 식별이 될 수 있는데 이는 안토시아닌의 축적 때문이다. 이러한 연구 결과는 앞으로 '캠벨얼리'의 형질전환 효율 향상에 있어 유용하게 이용될 수 있을 것이다.